Islamic Fintech Innovation as an Instrument of Finansial Literacy and Inclusion in The Collection of Islamic Funds (ZISWAF) in Indonesia - Hani Meilita Purnama Subardi; Ismail Ruslan; Zaenuddin Zaenuddin; Pratiwi Kurniati; Luthfiah; Oriah Akir; Lulu Qomariyah (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2026)
Purpose: This study aims to analyze the forms of fintech innovation developed by zakat management institutions, namely BAZNAS, Rumah Zakat, and Dompet Dhuafa, and to examine the contribution of Islamic financial technology (fintech) in enhancing financial literacy and inclusion in the collection of Islamic social funds (ZISWAF) in Indonesia amid the rapid growth of digital technology. Design/methodology/approach: This study employs a Systematic Literature Review (SLR) approach by reviewing 24 national and international journals with ISSN/E-ISSN published between 2021 and 2025. The data were collected through Google Scholar and analyzed systematically to identify patterns, innovations, and the role of fintech in Islamic social fund collection. Research Findings: The findings reveal that zakat institutions such as BAZNAS, Rumah Zakat, and Dompet Dhuafa have developed various digital innovations, including online zakat applications, Islamic e-wallets, zakat calculators, and real-time reporting systems to improve transparency and accessibility. Furthermore, Islamic fintech significantly contributes to increasing public participation through digital education, strengthening muzakki trust, and improving the effectiveness and efficiency of ZISWAF collection. Contribution/Originality/Novelty: This study contributes to the growing literature on Islamic fintech by providing a comprehensive review of digital innovations implemented by zakat institutions and highlighting the role of fintech in strengthening literacy and inclusion in Islamic social finance. The study also emphasizes the importance of collaboration among zakat institutions, regulators, and digital service providers to achieve sustainable zakat literacy and inclusion aligned with sharia principles.